Impact of music performance anxiety on cardiovascular blood pressure responses, autonomic tone and baroreceptor sensitivity to a western classical music piano-concert - Moreno-Gutiérrez, Juan Ángel; de Rojas Leal, Carmen; López-González, Manuel Víctor; Chao-Écija, Alvaro; Dawid-Milner, Marc Stefan (Frontiers in Neuroscience, 2023)
Introduction Music Performance Anxiety (MPA) is a prevalent condition among musicians that can manifest both psychologically and physiologically, leading to impaired musical performance. Physiologically, MPA is characterized by excessive muscular and/or autonomic tone. This study focuses on the cardiovascular blood pressure responses, autonomic tone and baroreceptor sensitivity changes that occur during musical performance due to MPA. Methods Six professional pianists perform a piece for piano written only for the left hand by Alexander Scriabin. The following parameters have been studied during the performance: ECG, non-invasive beat to beat continuous arterial blood pressure and skin conductance. Sympathetic and parasympathetic autonomic flow was studied with Wigner-Ville analysis (W-V) from R-R ECG variability, and baroreceptor sensitivity with the Continuous Wavelet Transform (CWT). Results During the concert a significant increase of heart rate, systolic, mean and diastolic arterial pressure were observed. No significant differences were found in skin conductance. The W-V analysis, which studies frequency changes in the time domain, shows a significant increase of sympathetic flow and a decrease of parasympathetic flow during the concert which is associated with a significant decrease in sympathetic and vagal baroreceptor sensitivity. Discussion The study of cardiac variability using the Wigner-Ville analysis may be a suitable method to assess the autonomic response in the context of MPA, and could be used as biofeedback in personalized multimodal treatments.